Diagnóstico de los factores críticos de éxito del ecosistema de emprendimiento en el Cantón Bolívar. - Moreno Zambrano, Luis Eduardo (2018)
This research was developed in Bolívar canton aimed at entrepreneurs and entrepreneurship associations, in order to make a diagnosis of the critical success factors of the entrepreneurship ecosystem, to potentiate them to the point of achieving positive results in the positioning of the market, the products and services they offer; that is why techniques were applied such as the survey where a questionnaire was developed for 63 entrepreneurs with the objective of knowing the current situation of the enterprises, on the other hand the interview allowed to analyze the government support given to the entrepreneurs, likewise, the SWOT matrix tool was used, which identified the strengths, opportunities, weaknesses and threats of the ventures. On the other hand, for the development of this research was carried out through four phases, first diagnosed the current situation of critical success factors such as access to physical infrastructure, government policies, financial support, opening to the internal market, commercial infrastructure, education, social and cultural norms; second the characteristics of the entrepreneurs were identified according to their activity that allowed to detect the main problems that affect the growth of the enterprises; third, strategies were proposed based on the critical factors; finally, a plan of improvement that suggests the formation of entrepreneurs in the legal framework that governs them, promotion and marketing, application of technology and a socialization campaign to raise awareness of the importance of entrepreneurship for economic growth.